Help to break out terms in an equation

alexanderthelinus

New member
Joined
Feb 26, 2015
Messages
1
How do I break out the p's in the following equation? So that the equation looks like this: p=... Thanks for you help!! If you could show it in a few steps I'd be really glad.

X=(P*Z+(1-P)*S)*e

Thanks,

Alex
 
How do I break out the p's in the following equation? So that the equation looks like this: p=... Thanks for you help!! If you could show it in a few steps I'd be really glad.

X=(P*Z+(1-P)*S)*e

Thanks,

Alex

First simplify the inner-most parenthesis → (1-P)*S
 
Top